+0  
 
+2
42
1
avatar+63 

simplify the expression

BabyChimChim  Sep 18, 2018

Best Answer 

 #1
avatar+1848 
+3

5*7p=35p

5*5=25

-3*1=-3

-3*10p=-30p

Plug those in: 35p+25-3+30p

+30p because the subtract and negative sign cancel out and become positive so we are adding now.

35p+30p=65p

25-3=22

65p+22 is your final expression.

RainbowPanda  Sep 18, 2018
 #1
avatar+1848 
+3
Best Answer

5*7p=35p

5*5=25

-3*1=-3

-3*10p=-30p

Plug those in: 35p+25-3+30p

+30p because the subtract and negative sign cancel out and become positive so we are adding now.

35p+30p=65p

25-3=22

65p+22 is your final expression.

RainbowPanda  Sep 18, 2018

26 Online Users

avatar
avatar
avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.